Effect of Human Resources Management on the Quality of Services Based on Hospital Accreditation - Hojjat Vahdati; Ali Hozni; Mehrnaz Tohidi Moghaddam (Shahid Sadoughi University of Medical Sciences, 2017)
Background: The quality of services is the most important determinants of successful hospital in competitive world. The aim of this study was to investigate the effect of human resource management based on hospital accreditation standards on the quality of hospital services using SERVQUAL model. Methods: The method of this research  In terms of purpose, was functional and applied, In terms of data collection, was descriptive, statistical community includes 310 family hospital clinical personnel in Rasht at fall of 2016, This sample was selected randomly, based Morgan table evaluated 175 persons. For data collection standard questionnaires Based on Iran's Ministry of Health and SERVQUAL used, for Information analysis, structural equation modeling with partial least square method was used with the Smart PLS2 software. Results: Test hypotheses suggest that empowering human resources management based on the accreditation standards for hospitals affects the quality of hospital services significantly. The most important factors in the management and empowerment of human resources include: education and empowerment of employees (0.950), policies and methods (0.949), safety and occupational health and environmental health guideline book (0.938). Conclusion: In order to improve the quality of hospital services as accreditation view, it is important notice to the management and empowerment of human resources items and it is suggested that hospital managers consider it to be the priority of their programs